Death by French roast - Erickson, Alex (Erickson, Alex. Bookstore café mystery., 2020)
" Krissy's helping a friend clean out her late mother's house when she learns that although the deceased died peacefully at an advanced age, her brother did not. In fact, Wade was killed more than thirty years ago, and the case was never closed. What surprises Krissy even more is that she has a personal connection to the story--her friend Rita was seeing Wade at the time, scandalizing the town with the couple's large age difference. With an older Rita now part of Krissy's writing group--and another member with police experience--she starts digging up gossip, talking to the victim's local coffee klatsch, and trying to find real clues amid the old rumors. But things just seem to grow muddier as she fights to identify whodunit . . ."--Amazon.